ANALISIS CRYPTOCURRENCY BERDASARKAN PRESPEKTIF EKONOMI SYARI’AH - Iiz Izmuddin; Elvi Nasriandani (Jurnal Ekonomi dan Bisnis, 2024)
The impact of using cryptocurrency when viewed from the perspective of Indonesian law can trigger various crimes that cause losses in several areas, one of which is in the economic sector. The problems that arise are that prices fluctuate, there are triggers for money laundering, and several problems from the opinions of ulama such as gharar, non-fulfillment of sil'ah and so on. The type of research used in this research is Library Research or library research. Carried out using library literature and documents from previous research. According to the type of data and analysis, qualitative research is carried out which emphasizes research and description in analyzing meaning. The aim of this research is a deep and broad understanding of the matter being studied. The source of information for this research comes from social media and journals. The results of this research are that crypto has a higher risk of loss and volatility, and is susceptible to money laundering. Then According to Nobel prize winning Economist and Columbia University professor Joseph Stiglitz cryptocurrency can be involved in money laundering. According to NU, cryptocurrency is obliged to pay zakat with the assets stored on the card. According to Muhammadiyah, the law on cryptocurrency depends on whether it is used for good or evil, but tends to prohibit it because cryptocurrency has not been recognized by the state as a medium of exchange, scale or commodity. Not to mention, cryptocurrency fluctuation numbers can change drastically in a short time. Meanwhile, the Fatwa of the Indonesian Ulema Council is of the opinion that crypto is prohibited unless the sil'ah requirements are met because it contains gharar, dharar, qimar and does not fulfill the sil'ah requirements, namely that it has a physical form, has value, the exact amount is known, has ownership rights and can be handed over to the buyer.